Karakteristik Sifat Kimia Tanah di University Farm Stasiun Bener Meriah - Manfarizah Manfarizah; Syamaun Syamaun; Siti Nurhaliza (Fakultas Pertanian, Universitas Syiah Kuala, 2011)
The Characteristics of Soil Physical Properties at the University Farm Station Bener MeriahABSTRACT. The University Farm Bener Meriah located in Tunyang village, Timang Gajah sub-district, Bener Meriah district, has the area of 76.37 ha. The site is allocated as the Bener Meriah Campus of Syiah Kuala University. The University Farm Station has functional as research centre, education and training for farmers, practice field for student, and training for farmers about organically managed of highland commodities. The aim of study are to characterize of soil physical properties and in the area of the University Farm Station Bener Meriah. The descriptive method was use in this research, by means of soil survey and direct observation in the field. The soil survey was carried out by a systematic method (grid system). Based on the research results, field observation, and the analysis of soil physical properties in laboratory, soil physical properties of the area of the University Farm Station were soil texture consisted of sandy loam, loam, and sit loam, soil aggregate stability index ranged from less stable (46.46 – 46.56) to stable (65.40 – 73.90), soil permeability comprised of moderate (2.16 – 4.50 cm h-1), moderately rapid (6.25 – 7.19 cm h-1), and rapid (13.33 cm h-1), soil water content ranged from 31.02 to 37.82%, soil bulk density ranged from 0.82 to 1.16 g cm-3, and soil porosity ranged from 52.56 to 75.34%.